A Miniaturized Metamaterial-Based Dual-Band 4×4 Butler Matrix With Enhanced Frequency Ratio for Sub-6 GHz 5G Applications - ABDULKADIR BELLO SHALLAH, ABDULKADIR BELLO SHALLAH; FARID ZUBIR, FARID ZUBIR; MOHAMAD KAMAL A. RAHIM, MOHAMAD KAMAL A. RAHIM; NOORLINDAWATY MD. JIZAT, NOORLINDAWATY MD. JIZAT; ABDUL BASIT, ABDUL BASIT; MAHER ASSAAD, MAHER ASSAAD; HUDA A. MAJID, HUDA A. MAJID (Ieee Acces, 2024)
This paper introduces an innovative 4 × 4 dual-band Butler matrix (BM) characterized by compactness and an enhanced frequency ratio (K). The design employs meandered lines and an interdigital capacitor (IDC) unit-cell-based composite right/left-handed transmission-line (CRLH-TL) metamaterial (MTM) structure. The BM integrates compact dual-band 3 dB branch-line couplers (BLC), a 0 dB crossover, and dual-band ±45◦ phase shifters on a single Rogers RT5880 substrate having relative permittivity εr of 2.2 and thickness h of 0.787 mm. Simulations and measurement results demonstrate reflection and isolation coefficients exceeding −20 dB at all ports, with obtained insertion loss of −6±3 dB over the 0.7 GHz and 3.5 GHz frequency bands. The achieved output phase differences of ±45◦ , ±135◦ , ±135◦ , and ±45◦ at the designed frequencies indicate a maximum average phase tolerance of ±4.5◦ concerning the ideal values. Importantly, the BM’s overall dimensions are 143 mm × 186 mm, resulting in an impressive 78% size reduction compared to traditional T-shaped BM designs. The proposed configuration is designed and simulated using CST Microwave Studio, with the agreement between simulated and measured parameters highlighting design reliability and effectiveness. Additionally, a performance evaluation comparing the proposed BM with existing circuits reveals its suitability for sub-6 GHz 5G dual-band antenna array beamforming networks (BFN) due to its compact size and improved band ratio.